New Therapeutic Approaches to Liver Fibrosis: A Practicable Route? - Zardi, Enrico Maria; Aldo, Dobrina; Giovanni, Ambrosino; Domenico, Margiotta; Francesco, Polistina; Antonella, Afeltra (Current Medicinal Chemistry, 2008)
The progress of research on the molecular pathogenesis of liver fibrosis and the consequent discoveries are likely to open new possibilities for therapeutic approaches to the management of this disease in the future. A key step towards this goal is a deeper comprehension of both the complex molecular and cellular mechanisms and the signaling involved in the development of hepatic fibrosis. It is not yet clear, in fact, what role apoptosis, cytokines, oxidants and other molecules play and what relationships exist between them in favouring or delaying the onset of these adverse mechanisms. At present, a unique mechanism is recognized to be the main reason for the cause and development of liver fibrosis: sustained hepatic stellate cell activation and transformation. Therefore, in this review, after considering the cause, development of fibrosis and interrelation between molecular and cellular profibrotic mechanisms, the part played in counteracting both of these actions by some anti-oxidants and anti-fibrotic molecules such as cytokines, prostacyclin and others will be taken into consideration. The gene therapy and the possible therapeutic use of liver stem cells and tissue engineering will also be dealt with briefly. At the moment, however, the efficacy of these novel strategies still needs to be further validated in animal studies and confirmed in clinical trials. Some data that are already available from in vitro and animal studies demonstrating the effectiveness of novel approaches to inhibiting or treating liver fibrosis can only offer moderate hope.
Keywords: Hepatic stellate cells